Critical success factors for e-learning at university and college level in the frame of EMVITET project - Nguyen , Thi Hai Van; Truong, Thi Thu Ha; Nguyen, Thanh Lam; Nguyen, Thi Le; Ho, Thi Quynh Nhu; Tran , Thi Quynh Nhu; Do, Thu Thuy; Hoang , Tuan Nguyen (Journal of Technical Education Science, 2022)
E-learning has become a trend in university education around the world, especially in the context of the increasingly widespread and complicated COVID-19 epidemic over the last two years. Online teaching and learning are considered a temporary solution for the education industry nationwide. Teaching and learning online opens up many opportunities but also brings many challenges for students and lecturers. This study investigates the effect of critical success factors (CSFs) on e-learning at universities and colleges which are members of the EMVITET project. Five categories were firstly identified via the literature and a questionnaire using the Likert scale was then carried out to evaluate the importance of each factor from students’ perspectives. Analytical results indicated 25 CSFs that influence the success of e-learning. Internet quality, self-efficacy, learning materials. are available and up-to-date, enthusiasm while teaching, and Content and property of subject are the top five influential factors that impact the e-learning success. This study, thus, supports leaders and teachers at universities and colleges in making decisions and strategies about e-learning.